Cyclooxygenase-2 expression in squamous cell carcinoma of the uterine cervix is associated with lymph node metastasis - Surapan Khunamornpong (2018)
Objectives: Previous studies have indicated that cyclooxygenase-2 (COX-2) activity is related to the development and progression of cervical cancer. In this study, we evaluated the association between COX-2 expression and specific clinicopathologic features in surgically-treated squamous cell carcinoma of the uterine cervix. Methods: Immunohistochemical staining for COX-2 was performed on 196 cases of stage IB-IIA cervical squamous cell carcinoma. Results were correlated with the clinicopathologic features and disease-free survival using statistical analysis. Results: Expression of COX-2 was detected in 48.5% of cases. COX-2 expression was significantly associated with lymph node metastasis (p = 0.045) but lacked significant correlation with tumour stage, size, histologic grade, deep stromal invasion, lymphovascular space invasion, and parametrial involvement. In multivariate analysis, only parametrial involvement and lymphovascular space invasion (LVSI) were independent predictors for lymph node metastasis (p = 0.001 and 0.007, respectively). COX-2 expression was not associated with lymph node metastasis in the absence of parametrial involvement or LVSI. In the cases with LVSI, COX-2 expression was significantly associated with lymph node metastasis (p = 0.03), although with marginal significance (p = 0.068) in the multivariate analysis. COX-2 expression was not associated with a decrease in disease-free survival for patients overall (p = 0.977). However, in patients who did not receive adjuvant treatment, COX-2 expression was significantly associated with decreased disease-free survival (p = 0.008) and was a significant predictor of recurrence (p = 0.014). Conclusions: In this study, COX-2 expression was associated with lymph node metastasis in cervical squamous cell carcinoma, but this was linked to the presence of LVSI or parametrial involvement. This suggests that COX-2 expression may enhance lymph node metastasis after LVSI occurs. If so, immunohistochemical staining for COX-2 may provide additional prognostic information in LVSI-positive cases, in particular in patients who do not receive postoperative adjuvant treatment. © 2008 Elsevier Inc. All rights reserved.